Subfamily Mantispinae Enderlein, 1910 (Insecta: Neuroptera) in India - Kaur, Simarjit; Pandher, Manpreet Singh; Chandra, Kailash; Dubey, Anil Kumar (Zootaxa, 2021)
The present paper adds to the knowledge of the family Mantispidae from India. Herein we describe two new Euclimacia species: E. similis sp. nov. from Madhya Pradesh and E. nicobarica sp. nov. from Andaman & Nicobar Islands. A new combination is also proposed: Mantispilla coorgensis (Ohl, 2004a) comb. nov. With these additions, the family is now represented in India by 22 species in eight genera.